Characterization of a Cardiorenal-like Syndrome in Aged Chimpanzees (Pan troglodytes). (March 2016) - Chilton, J.; Wilcox, A.; Lammey, M.; Meyer, D.
Cardiorenal syndrome involves disease and dysfunction of the heart that leads to progressive renal dysfunction. This study investigated the relationship between cardiac and renal disease in 91 aged chimpanzees at the Alamogordo Primate Facility by evaluation of the medical histories, metabolic parameters, functional measurements of the cardiovascular system, clinical pathology, and histopathology focused on the heart and kidney. Cardiac fibrosis was the most frequent microscopic finding in 82 of 91 animals (90%), followed by glomerulosclerosis with tubulointerstitial fibrosis in 63 of 91 (69%). Cardiac fibrosis with attendant glomerulosclerosis and tubulointerstitial fibrosis was observed in 58 of 91 animals (63%); there was a statistically significant association between the 2 conditions. As the severity of cardiac fibrosis increased, there was corresponding increase in severity of glomerulosclerosis with tubulointerstitial fibrosis. Altered metabolic, cardiovascular, and clinical pathology parameters indicative of heart and kidney failure were commonly associated with the moderate to severe microscopic changes, and concurrent heart and kidney failure were considered the cause of death. The constellation of findings in the chimpanzees were similar to cardiorenal syndrome in humans.